Sources, Distribution and Paleoenvironmental Application of Fatty Acids in Speleothem Deposits From Krem Mawmluh, Northeast India - Kalpana, M. S.; Routh, Joyanto; Fietz, Susanne; Lone, Mahjoor A.; Mangini, Augusto (Frontiers in Earth Science, 2021)
Integrated multiproxy geochemical studies are essential to reconstruct the paleoenvironment through different time scales. Pristine terrestrial archives such as speleothems provide an excellent opportunity to study these changes by measuring the stable isotope and biomarker trends preserved in these records. Here, we investigated fatty acids in drip water, moonmilk, and a stalagmite (KM-1) retrieved from Krem Mawmluh in northeast India to constrain the sources and distribution of these compounds. Besides, we tested their compatibility with established glycerol dialkyl glycerol tetraethers and stable isotope proxies in KM-1 to probe the use of fatty acid-derived proxies for paleoclimate reconstruction. We observe a similar composition of fatty acids in drip water as well as the cave deposits with significantly higher concentrations of fatty acids in drip water (10.6–124 μg/L) and moonmilk (1.32–16.5 μg/g) compared to the stalagmite (0.67–2.09 μg/g). In KM-1 stalagmite, fatty acids and the presence of azelaic acid transported from surface soils indicate that these compounds are derived from bacterial activity both within the cave and the overlying soil cover. The branched C15 fatty acid index (iso+anteiso C15/nC15) increases during the Holocene, suggesting enhanced microbial production under warm/wet conditions. Fluctuations in the fatty acid indices coincide with abrupt shifts in the TEX86 and BIT proxies reflecting the warm/wet Holocene and cold/dry Late Pleistocene. These trends imply the potential use of fatty acids for reconstructing past climate changes in speleothems but need more analytical reference points to provide statistical data.